2024
DOI: 10.18063/ijb.v7i1.300
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation, Antibacterial Performance, and Cytocompatibility of a Novel ZK30-Cu-Mn Biomedical Alloy Produced by Selective Laser Melting

Abstract: An antibacterial biomedical Mg alloy was designed to have a low biodegradation rate. ZK30-0.2Cu-xMn (x = 0, 0.4, 0.8, 1.2, and 1.6 wt.%) was produced by selective laser melting (SLM). Alloying with Mn had a significant influence on the grain size, hardness, and biodegradation rate. Increasing Mg content to 0.8 wt% decreased the biodegradation rate, attributed to the decreased grain size and the relatively protective manganese surface oxide layer. Higher Mn contents increased the biodegradation rate attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Chemical composition of material is another key factor affecting grain size. Up to now, the effects of Al [43,79], Mn [93][94][95], Zn [44], Cu [92,96], Ce [97], Dy [98] on the grain size of additively manufactured magnesium alloys have been investigated. The results demonstrated that the addition of Al, Cu, Zn, Ce and Dy can significantly refine the grains, and the grain size decreases monotonically with the content increase of these elements.…”
Section: Microstructure Characteristicsmentioning
confidence: 99%
“…Chemical composition of material is another key factor affecting grain size. Up to now, the effects of Al [43,79], Mn [93][94][95], Zn [44], Cu [92,96], Ce [97], Dy [98] on the grain size of additively manufactured magnesium alloys have been investigated. The results demonstrated that the addition of Al, Cu, Zn, Ce and Dy can significantly refine the grains, and the grain size decreases monotonically with the content increase of these elements.…”
Section: Microstructure Characteristicsmentioning
confidence: 99%
“…Generally, alloying Mg with different elements or incorporating it with some polymers such as polylactide- co -glycolide (PLGA)/tricalcium phosphate (TCP) enhances strength and lowers the degradation rate [ 108 , 110 ]. Xie et al [ 111 ] suggested that alloying Mg with manganese (Mn) can decrease the biodegradation rate mostly due to the formation of a Mn oxide film on the surface (acting as a protective layer). Incorporating Mn into Mg alloys decreased the metal grain size that can be attributed to the enhanced number of nucleation sites.…”
Section: Metallic Biomaterials For Additive Manufacturingmentioning
confidence: 99%
“…Laser melting cools remarkably fast upon solidification due to its rapid melting rate. This is because the material powders begin rapid in situ cooling in the melt pool [11,12]. Therefore, both microwave sintering and laser melting can easily produce fine grain sizes, and thus are expected to produce pure iron with an increased degradation rate.…”
Section: Introductionmentioning
confidence: 99%